Mining for Posttraumatic Growth (PTG) in Sexual Minority Women Who Survive Intimate Partner Violence: A Conceptual Perspective. - Counselman-Carpenter, Elisabeth; Redcay, Alex (Behavioral Sciences, 2018)
This theoretical paper explores the need to use posttraumatic growth (PTG) as a framework when studying sexual minority women (SMW) who are survivors of intimate partner violence (IPV) to examine the relationship between risk factors such as stress, anxiety and alcohol use and to understand the role of protective factors through mining for the presence of posttraumatic growth (PTG). Despite a call for continued research in this highly vulnerable population, representative studies of SMW and PTG remain extremely limited. Research that examines the relationship between IPV, behavioral health issues, and posttraumatic growth would provide the opportunity to develop tailored intervention models and opportunities for program development to decrease isolation and increase factors of posttraumatic growth. In particular, the impact of how interpersonal relationships as potential mediators and/or outcomes of posttraumatic growth (PTG) needs to be explored more thoroughly. PTG is a valuable framework for vulnerable populations such as sexual minority women because it focuses on how transformative change may result from traumatic experiences such as surviving IPV.
3 citations (Crossref) [2023-10-31] Place: Switzerland Counselman-Carpenter, Elisabeth. Department of Social Work, Southern Connecticut State University, New Haven, CT 06515, USA. counselmane1@southernct.edu. Redcay, Alex. School of Social Work, Millersville University, Millersville, PA 17551, USA. alexredcay@gmail.com.
Keywords: Intimate partner violence; Post-traumatic growth; Sexual minority women; dept.swk; intimate partner violence; peer-reviewed; sexual minority women

Understanding the role of the brick-and-mortar classroom in course design and implementation of the “flipped” classroom: An exploratory case study - Counselman-Carpenter, Elisabeth; Redcay, Alex (Journal of Teaching and Learning with Technology, 2019)
1 citations (Crossref) [2023-10-31]
Keywords: dept.swk; peer-reviewed

The impact of fluid attraction and fluid identity on mental health - Redcay, Alex; Counselman-Carpenter, Elisabeth; Proctor, Curtis (Journal of Gay & Lesbian Mental Health, 2019)
Using data from the National Longitudinal Study of Adolescent Health, this study examined the impact of sexuality factors and satisfaction with partner on stress, anxiety, and depressive symptoms. Multiple regression was used to evaluate the impact of predictors such as sexuality factors and relationship satisfaction on the dependent variables: stress, anxiety, and depression. Three main results were discovered. First, sexual minority females who have lower levels of education and are dissatisfied with their relationship experience significantly higher stress, while sexual minority males do not differ from heterosexual males in terms of relationship satisfaction or stress. Second, sexual minority females who have lower levels of education and who are dissatisfied with their relationship experience significantly higher anxiety, while sexual minority males do not differ from heterosexual males in terms of relationship satisfaction or anxiety. Finally, female sexual minorities who have lower levels of education reported fluid attraction, fluid identity, dissatisfaction with their relationship, and have significantly higher depression when compared to male sexual minorities or heterosexuals. Further research should examine gender and fluidity in greater detail. © 2018, © 2018 Taylor & Francis Group, LLC.
1 citations (Crossref) [2023-10-31]
Keywords: Anxiety; depression; dept.swk; fluid attraction; fluid identity; peer-reviewed; satisfaction with partner; sexual orientation; stress

“My sister is the one that made me stay above water”: How social supports are maintained and strained when survivors of intimate partner violence reside in emergency shelter programs - Stylianou, Amanda M.; Counselman-Carpenter, Elisabeth; Redcay, Alex (Journal of Interpersonal Violence, 2018)
While social support is critical in helping intimate partner violence (IPV) survivors heal and build hope, social isolation is a frequent experience for survivors. For survivors residing in domestic violence (DV) emergency shelters, the isolation from social supports is often exacerbated by shelter rules and policies. This study uses a 20th century feminist framework to understand the ways in which social support networks are maintained and/or strained when survivors reside in DV emergency shelters. Among this sample of 76 survivors, 40 participants identified family members as their support system, with siblings and mothers most frequently identified, and 14 participants identified friends as their social support. Prior to entering the DV shelter, survivors reported that their support networks provided encouragement and motivation along with emotional support, financial and material support, and support with children. Participants spoke about the process of informing their support systems of the transition into a DV shelter, the positive and negative impacts of the transition on their support system, and the roles that frequent telephone calls and texts played in maintaining their support networks. Participants reported positive impacts of residing in a DV shelter including improved emotional and physical health, strengthened emotional relationships, and improved physical and emotional resource provision. For those participants reporting negative experiences, they frequently identified logistical barriers, including the inability to receive visitors at the shelter, the distance between them and their friends and family, and strict rules around curfew and child care. Our findings invite researchers and practitioners to consider further examination of best practices around programming that supports survivors in maintaining social supports while residing in shelter programs
6 citations (Crossref) [2023-10-31]
Keywords: dept.swk; peer-reviewed

The Arc of Justice: Examining Policies and Laws to Advance the Human Rights of Transgender and Gender Expansive Children - Redcay, Alex; Counselman-Carpenter, Elisabeth; McMahon, Sheila; Luquet, Wade; Rice, Karen; Lance, Roseanna (Journal of Human Rights and Social Work, 2019)
The role of the social worker in the achievement of human rights is to assist individuals in their struggle for dignity and their attainment of their full potential. Ethical social work ensures just laws and practices that allow all persons to live without discrimination. The purpose of this paper is to present the practice and policy implications of the last five years of court cases regarding transgender and gender expansive (TGE) children and school systems in the USA. This paper outlines the legal justifications for revisions to the current procedures and policies of interacting with TGE children, including use of restrooms consistent with gender identity (RCGI). These recommended guidelines are designed to prevent ongoing human rights violations and create pathways for TGE children to live their lives congruently with their gender identity. Basic human rights for the TGE individual include policy improvements involving restrooms, locker rooms, showers, overnight accommodation, affirmed name, and identification for the child welfare, mental health, educational, medical, juvenile justice, and law enforcement systems. © 2019, Springer Nature Switzerland AG.
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/135-631-118-549-565, pop00305
Keywords: Ethics; Gender expansive children and youth; Policy; Transgender; dept.swk; peer-reviewed